Safety and feasibility of anlotinib in children with high risk, recurrent or refractory sarcomas: an open-label, single-centre, single-arm, phase Ia/Ib trialResearch in context - Suying Lu; Yi Que; Dongyang Liu; Feifei Sun; Xueting Yao; Liting Deng; Jing Zhan; Junting Huang; Ruiqing Cai; Xin Wang; Shixing Zhu; Zijun Zhen; et al. (EClinicalMedicine)
Summary: Background: Anlotinib is a novel highly potent multitargeted tyrosine kinase inhibitor. However, the safety, recommended dosage, pharmacokinetics (PK) characteristics, and efficacy of anlotinib in paediatric patients have not been fully studied. We aimed to evaluate the safety, PK, and feasibility of anlotinib in children with high risk, recurrent or refractory sarcomas. Methods: This was an open-label, single-centre, single-arm, phase I study utilizing a “3 + 3” design. Participants were recruited at the Sun Yat-sen University Cancer Centre in China. Paediatric patients aged 5–18 years with a diagnosis of high-risk, relapsed, or refractory sarcomas were eligible for enrolment in this study. Anlotinib was administered orally once daily on a 2-week-on/1-week-off schedule. Treatment continued until disease progression, death, unacceptable toxicity, or withdrawal of consent for any reason. For patients receiving anlotinib as maintenance therapy, the maximum treatment duration was one year. The primary endpoint of phase Ia was the maximum tolerated dose (MTD) of anlotinib. The primary endpoint of phase Ib was the recommended phase II dose (RP2D) of anlotinib. Secondary endpoints included safety, PK, and efficacy. Efficacy endpoints, such as objective response rate (ORR), disease control rate (DCR), progression-free survival (PFS), and overall survival (OS), were assessed at every 2 cycles for patients with measurable lesions until disease progression or intolerable toxicity. Patients with a complete response (CR) at baseline were assessed every 4 cycles until disease progression, or intolerable toxicity, or upon completion of one year of treatment. The primary analysis included all participants who received at least one dose of anlotinib, following the per protocol approach. The safety analysis included all participants who received at least one dose of anlotinib and were monitored for adverse events during the treatment period. This study is registered with ClinicalTrials.gov, NCT04659733. Findings: Between December 29, 2020, and September 7, 2022, 34 patients were enrolled for toxicity. Among them, 61.8% (21/34) patients were evaluable for efficacy, and 38.2% (13/34) received anlotinib as maintenance therapy. Two patients (5.9%) experienced dose-limiting toxicities, including grade 3 hematuria and grade 3 hand-foot syndrome. AEs were reported in all patients, with most being grade 1 or 2 in severity. The most common AEs of any grade were hypothyroidism (58.8%, 20/34), diarrhoea (41.2%, 14/34) and abdominal pain (38.2%, 13/34). No grade 4 or treatment-related deaths occurred. PK analysis indicated a significant correlation between abdominal pain and higher steady-state trough concentrations [OR 1.08 (95% CI: 1.01–1.17), P = 0.04] as well as AUCτ [OR 1.00 (95% CI: 1.00–1.01), P = 0.04]. The MTD and RP2D of anlotinib for paediatric patients (5–18 years) was 8 mg for those under 35 kg and 12 mg for those 35 kg or more. The ORR and DCR for evaluable patients were 0% (95% CI: 0%–0%) and 52.4% (95% CI: 29.1%–75.7%), respectively. The 2-year PFS and OS rates for patients who received anlotinib as maintenance therapy were 84.6% (95% CI: 51.2%–95.9%) and 92.3% (95% CI: 56.6%–98.9%), respectively. Interpretation: Anlotinib was well tolerated in paediatric patients. Our findings provide preliminary evidence of the efficacy of anlotinib as a maintenance therapy in paediatric patients with high risk, relapsed/refractory sarcoma who achieved a CR. Further investigation of anlotinib in larger, controlled studies is needed to determine its clinical utility. Funding: The National Key Research and Development Program of China, the National Science and Technology Major Projects, the National Natural Science Foundation of China, the Young Science and Technology Talent Support Program of Guangdong Precision Medicine Application Association, and Capital’s Funds for Health Improvement and Research.